Patient expectations and satisfaction with non-surgical periodontal treatment provided by fourth-year dental students at the University of Otago, Faculty of Dentistry, Dunedin - Liu, Cindy; Le Pine-Day, Michael; Al-Naasan, Zeina; Tawse-Smith, Andrew (IIUM Journal of Orofacial and Health Sciences, 2025)
Evaluation of patient satisfaction is critical to assessing the quality of care. In New Zealand, there are limited studies evaluating the satisfaction of patients receiving treatment by dental students. The aim of this study was to evaluate the current patient satisfaction levels and the factors that influence patient satisfaction with non-surgical periodontal treatment provided by fourth-year dental students at the University of Otago Faculty of Dentistry, along with areas requiring improvement. This study utilised a mixed-methods approach. A 29-item electronic survey was completed by 41 eligible participants. A five-point Likert scale was used to ascertain respondents' level of agreement with a range of statements related to quality of care. Open text fields were used after each group of questions to allow participants to expand on their responses. Quantitative data was analysed using SPSS and qualitative data was coded and content analysed. 100 percent of respondents agreed that they received good periodontal treatment and 81.6 percent agreed that their dental student appeared competent. Participants further elaborated on areas that can be improved such as logistics, standard of care, patient expectation, prior knowledge, communication, physical and emotional care, personnel, technical skills, and physical space. Despite limitations, this study indicated a high level of patient satisfaction with the periodontal treatment provided. Areas of improvement include access to care, informed consent, and communication. The results of this survey reinforce the excellent standard of care provided by students and highlight areas for improvement in future years.